Halo abundance and assembly history with extreme-axion wave dark matter at z ≥ 4. (2nd October 2017) - Schive, Hsi-Yu; Chiueh, Tzihong
Abstract: Wave dark matter (ψDM) composed of extremely light bosons ( m ψ ∼ 10 − 22 eV), with quantum pressure suppressing structures below a kpc-scale de Broglie wavelength, has become a viable dark matter candidate. Compared to the conventional free-particle ψDM (FPψDM), the extreme-axion ψDM model (EAψDM) proposed by Zhang & Chiueh features a larger cut-off wavenumber and a broad spectral bump in the matter transfer function. Here, we conduct cosmological simulations to compare the halo abundances and assembly histories at z = 4–11 between three different scenarios: FPψDM, EAψDM and cold dark matter (CDM). We show that EAψDM produces significantly more abundant low-mass haloes than FPψDM with the same m ψ, and therefore could alleviate the tension in m ψ required by the Lyα forest data and by the kpc-scale dwarf galaxy cores. We also find that, compared to the CDM counterparts, massive EAψDM haloes are, on average, 3–4 times more massive at z = 10–11 due to their earlier formation, undergo a slower mass accretion at 7 ≲ z ≲ 11, and then show a rapidly rising major merger rate exceeding CDM by ∼ 50 per cent at 4 ≲ z ≲ 7. This fact suggests that EAψDM haloes may exhibit more prominent starbursts at z ≲ 7.